The role of consumerism in driving inflation: A literature review on the digital economy (2020-2024) - Wahyuliana, Eka; Ruslan, Nur Jaya Baiduri (Institute of Accounting Research and Novation (IARN), 2024)
The Use of Digital Technology, Particularly in the Form of E-commerce and E-money, has Transformed the Way Consumers Interact with Markets and Products. This phenomenon has a significant impact on the inflation rate in the digital economy. This article aims to conduct a literature review on the role of consumers, e-commerce, and e-money in influencing inflation in the context of the digital economy. This literature review involves the analysis of various empirical, theoretical, and conceptual studies conducted between 2020-2024 by gathering relevant data from the official websites of Bank Indonesia (BI) and the Central Statistics Agency (BPS). From the research results, it is found that e-money and e-commerce have a significant influence on the inflation rate due to their easy, cheap, fast, and practical nature, which greatly facilitates transactions for the public. However, this triggers an increase in the level of consumerism in society, which impacts inflation. The results of this literature review are expected to provide a better understanding of the dynamics of inflation influenced by consumers in the digital economy.